SCREENING OF STRAINS OF THE FUNGUS BEAUVERIA BASSIANA FOR VIRULENCE AGAINST LARVAE OF LOCUSTA MIGRATORIA L. (Experimental biology, 2021)
The article provides a preliminary screening of Asian locust larvae aged 2-3 years for the virulence of 25 isolates isolated from insects belonging to different systematic groups of fungi Beauveria bassiana. Six of the 25 strains showed high biological activity against larvae, (BCo1-14, BSc1-15, BSc2-15, BTr1-16, BPit-16, BCa3(m)-09) reaching a mortality rate of 90-100% 21 days after inoculation. The strains that have the best effect on the level and rate of mortality of the host organism are - BCo1-14, BSc1-15, BSc2-15, BTr1-16, BPit-16, BCa3(m)-09. The greatest biological activity was observed in the BSc1-15 strain, as the mortality rate of test organisms was only 100% within 15 days of exposure. The lowest activity was shown by the BCi4-14 strain in the range of 35.0-62.5%. At the same time, the mortality rate of Asian locust larvae in the control variant (without treatment) for 21 days was 15.0±2.88%.
Keywords: еntomopathogen, virulent, Beauveria bassiana, strain, crop, Locusta migratoria migratoria L., conidia, fungi, screening